MODULATION OF ANGIOGENIC BALANCE DURING PREGNANCY BY EXOGENOUS HEPARIN. (April 2021) - Moore, Kyle; Chapman, Heather; George, Eric
Abstract : Objective: Preeclampsia is a pregnancy-specific hypertensive disorder, commonly believed to result from placental dysfunction. Increased soluble vascular endothelial growth factor receptor-1 (sFlt-1) is consistently observed, and is believed to be pathogenic. sFlt-1 contains a binding site for the extracellular matrix (ECM) component heparan sulfate and, therefore, the anticoagulant heparin. Here we hypothesized that infusion of unfractionated heparin during pregnancy in rodents would displace and solubilize ECM-bound sFlt-1, cause maternal angiogenic imbalance, and maternal hypertension. Design and method: To determine the effects of heparin on sFlt-1 release in vitro. BeWo cytotrophoblasts and rodent placental explants were cultured at normoxic (8%) or hypoxic (1%) oxygen with or without exogenous heparin (10U/ml). Media sFlt-1 was measured by commercial ELISA, membrane-bound sFlt-1 was determined by quantitative immunofluorescence, and mRNA levels of Flt-1, sFlt-1, and heparanase were monitored by qRT-PCR. Pregnant rats were treated from GD14–19 with i.p. unfractionated heparin (300U/kg/day) or saline. MAP was monitored by carotid catheter on GD19, when tissues were collected and morphometrics noted. Placental and plasma sFlt-1 and VEGF were determined by commercial ELISA. Results: In BeWo cells, heparin increased media sFlt-1 in both normoxic (p = 0.0002) and hypoxic samples (p = 0.0066) compared to controls. Total Flt-1 and sFlt-1 was significantly decreased in heparin treated cells compared to controls (p = 0.0063) by immunofluorescence. In placental explants, 10U/mL heparin for 30 minutes significantly increased media sFlt-1 levels (p = 0.0005). Flt-1 mRNA was significantly decreased (p = 0.003) in heparin treated samples, while sFlt-1 and HPSE showed trends towards reduction. Infusion of unfractionated heparin increased MAP in pregnant rats compared to controls (110 ± 2.6 mmHg vs. 99.6 ± 1.3 mmHg, respectively; p = 0.0038). Placental mass (p = 0.0116) and pup weight (p = 0.0075) decreased with heparin treatment. Placental sFlt-1 levels were reduced with heparin (761.8 ± 48.4 pg/mg vs. 913.8 ± 33 pg/mg; p = 0.0178), while placental VEGF levels trended toward reduction. Heparin treatment reduced plasma bioavailable VEGF levels compared to controls (1174 ± 38.5 pg/mL vs. 1492 ± 62.2 pg/mL, respectively; p = 0.0006). Conclusions: Heparin infusion released ECM-bound sFlt-1, altered the angiogenic balance in the placenta and circulation of pregnant rats, and elevated their mean arterial pressure.